2020
DOI: 10.1007/s40122-020-00180-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders and Headache: A Review of Correlation and Mutual Influence

Abstract: The review is devoted to the complex relationship between headache and sleep disorders. The shared neuroanatomical structures of the nervous system involved in pain perception and sleep are shown, and mechanisms of comorbidity between headaches and sleep disorders are considered. Various types of headaches in the continuum of the sleep–wake cycle are described. Both pharmacological and non-pharmacological approaches to treatment are examined in detail, with the biochemical basis of the drug action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 68 publications
0
21
0
2
Order By: Relevance
“…Up to half of headache patients appear to report various sleep disturbances and a significant relationship between headache and sleep is found when approximately 75% of cases of pain occur during sleep or immediately after waking up [ 16 , 17 , 18 ]. In most cases, sleep is a reliever of migraine attacks [ 19 , 20 ]. In a study based on an arctic population, sleep was the main protective factor against migraine attack.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to half of headache patients appear to report various sleep disturbances and a significant relationship between headache and sleep is found when approximately 75% of cases of pain occur during sleep or immediately after waking up [ 16 , 17 , 18 ]. In most cases, sleep is a reliever of migraine attacks [ 19 , 20 ]. In a study based on an arctic population, sleep was the main protective factor against migraine attack.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some patients with headache triggered or relieved by sleep demonstrate some behaviors, which predispose them to deepening sleep disturbances [ 29 ]. Sleep problems such as sleep deprivation, oversleeping, or lack of regularity could be an important factor in the transition from an episodic to chronic form of migraine [ 19 , 25 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among chronic pain conditions, chronic headaches are highly prevalent comorbid conditions with sleep disorders [ 8 , 9 ]. An earlier large epidemiological study [ 10 ] showed that 18.1% of the studied population had concurrent headache and insomnia, 16.3% only had headaches, and 21.1% only had sleep disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…The comorbidity between headaches and sleep disorders has been explained by shared neuroanatomical structures within the nervous system and neurobiological and psychological factors involved in both headaches and sleep disorders [ 8 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation